INOVASI PENGOLAHAN LIMBAH RUMAH TANGGA MENJADI PUPUK UNTUK PETANI DESA PUUBENUA - Ahmad Renaldi; Nira Handayani; Krisda Santika; Rini Adriani; Alders Paliling (Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
Household waste that is not managed properly can have a negative impact on the environment, especially in rural areas such as Puubenua Village, which does not have an adequate waste management system. One of the solutions offered to overcome this problem is to convert household waste into organic fertilizer, which is not only environmentally friendly but can also increase agricultural yields. The purpose of this activity is to provide training to the community on the processing of household waste into organic fertilizer, which is expected to reduce the volume of waste and farmers' dependence on chemical fertilizers. The methods used in this program include an initial survey to determine the condition of household waste in Puubenua Village, training in making organic fertilizer, and mentoring and monitoring for two months to ensure that the implementation of the program runs well. Data were collected through interviews and direct observation to evaluate the program's impact on the environment and agricultural productivity. The results of this program show that the processing of household waste into organic fertilizer has succeeded in reducing the volume of waste by up to 70%, as well as reducing the use of chemical fertilizers by farmers by up to 50%. In addition, public awareness of the importance of independent waste management has increased significantly, and the application of organic fertilizers has a positive impact on agricultural products. In conclusion, this program has succeeded in providing an effective solution to the household waste problem while improving the economic welfare of farmers. This program is expected to be implemented in other villages to support sustainable agriculture and environmentally friendly waste management